Facilitators, Barriers, and Structural Determinants of Physical Activity in Nulliparous Pregnant Women: A Qualitative Study - Leila Kianfard; Shamsaddin Niknami; Farkhonde Amin SHokravi; Sakineh Rakhshanderou (Hindawi Limited, 2022)
Aims & Backgrounds. Reduced physical activity in pregnant women is highly stemmed from their misconceptions and attitudes during pregnancy. This study is aimed at recognizing the facilitators, barriers, and structural factors that influence activity among pregnant women. Participants & Methods. This qualitative study was conducted from January to June 2020 in nulliparous pregnant women. Forty participants selected randomly from the Pounak Health Center of Tehran City, Iran, answered open-ended questions about the obstacles that deprived them of physical activity during pregnancy. Data were analyzed by MAXQDA 12 software. Findings. 620 primary codes, 42 secondary codes, 11 subthemes, and 6 themes were extracted. These themes were divided into the PEN-3 categories: facilitators, barriers, and structural factors. The nurture factors as facilitators had communication and support from others as subthemes. Barriers consisted of sociocultural (participate in pregnancy class with a companion, social beliefs, and culture of poverty), socioeconomic (financial problems), and individual factors (physical, psychoemotional, and spiritual dimensions), and structural factors consisted of environmental (equipment) and organizational (possibilities in health centers) factors. Conclusion. Lack of awareness and misinformation, accessibility obstacles, and economic problems are the worst physical activity barriers during pregnancy. Being among other pregnant women and the physicians' recommendations are the best facilitators of physical activity during pregnancy.